PEMANFAATAN SAUNG BACA SEBAGAI SARANA PENGUATAN GERAKAN LITERASI SEKOLAH (GLS) - Hana Nabilah; Rina Yuliana; Odin Rosidin (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
The purpose of this study was to determine the process of using Saung Baca as a means to improve the School Literacy Movement (GLS) at SDN 1 Muncang especially in the process of implementing literacy activities, the factors that support literacy activities, and the results of implementing literacy activities at SDN 1 Muncang by utilizing Saung Read. The approach and method used in this research is a descriptive qualitative approach. In collecting data, researchers used triangulation of techniques and sources. The results of the study indicate that in the process of implementing literacy activities by utilizing a reading room, the school prepares supporting facilities and infrastructure, an effective social environment, and a supportive school environment. Then literacy activities that are routinely carried out at Saung Baca, which are 15 minutes of reading and Friday Blessing. There are three factors that support literacy activities by utilizing Saung Baca, namely policies made by school principals related to literacy activities, provision of facilities and infrastructure that support literacy activities, and involvement of school residents during the implementation of literacy activities at Saung Baca. As for the results of the implementation of literacy activities by utilizing huts, it has an impact on three aspects, namely school literacy culture, student character values ​​and student learning achievement.